2020
DOI: 10.1093/schbul/sbaa095
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Hearing and Personification: Characterizing Social Qualities of Auditory Verbal Hallucinations in Early Psychosis

Abstract: Recent therapeutic approaches to auditory verbal hallucinations (AVH) exploit the person-like qualities of voices. Little is known, however, about how, why, and when AVH become personified. We aimed to investigate personification in individuals’ early voice-hearing experiences. We invited Early Intervention in Psychosis (EIP) service users aged 16–65 to participate in a semistructured interview on AVH phenomenology. Forty voice-hearers (M = 114.13 days in EIP) were recruited through 2 National Health Service t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 31 publications
4
63
0
Order By: Relevance
“…While the most common voice identity was 'unknown/strangers', all reported communicative intent from their voice (literal and in some cases also non-literal). Similarly, Alderson-Day et al (2021) found (within a sample attending an early intervention service) that 75% of voices recurred over time, had a distinct character, but were not related to a known person [i.e. experienced as an 'internally individuated agency' (Wilkinson & Bell, 2016)].…”
Section: Discussionmentioning
confidence: 99%
“…While the most common voice identity was 'unknown/strangers', all reported communicative intent from their voice (literal and in some cases also non-literal). Similarly, Alderson-Day et al (2021) found (within a sample attending an early intervention service) that 75% of voices recurred over time, had a distinct character, but were not related to a known person [i.e. experienced as an 'internally individuated agency' (Wilkinson & Bell, 2016)].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, participants with previous hallucinatory experiences scored relatively high in explicit recognition of their own voice (M=0.77, SD =0.32 for the egocentric, and M=0.78, SD = 0.27 for the allocentric condition), suggesting that this effect is not necessarily linked to lack of explicit self-recognition. Notably, auditory vocal hallucinations are often linked to a feeling of a presence (Alderson-Day et al, 2020), accompanied by bodily alterations (Alderson-Day et al, 2020;Woods et al, 2015), and appear to come from extracorporeal space (Copolov, 2004;McCarthy-Jones et al, 2014;Woods et al, 2015). These bodily and spatial aspects during auditory hallucinations are linked to primary characteristics of the bodily self.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not only 4 psychotic individuals seem more susceptible to alterations of bodily self-consciousness (Klaver & Dijkerman, 2016;B. Nelson et al, 2014), but prevalent symptoms in the condition are both auditory vocal hallucinations (Alderson-Day et al, 2020) and abnormal bodily self experiences (Di Cosmo et al, 2018;Nelson et al, 2013). These results point to a link between altered selfconsciousness and self-related auditory-vocal processes, which have, however, been seldom addressed directly in the above mentioned experimental research.…”
Section: Introductionmentioning
confidence: 98%
“…Even though, in the next section, we will point out a few further features of Carl's voices, the extracts we have discussed so far explain why, in Alderson-Day et al's binary classification, Carl was coded as a case of minimal personification. 2…”
Section: Carl's Voicesmentioning
confidence: 99%
“…1 Both people were interviewed about their voice-hearing experiences between 2017 and 2019, while they were using Early Intervention in Psychosis services provided by the UK's National Health Service in the North East of England. 2 As part of the interviewing process, these two individuals were given the pseudonyms 'Carl' and 'Orla'. In answer to the first interview question about how each person would describe the voices they have been hearing recently, Carl begins as follows: i Right, ehm, well I hear bangs in the walls.…”
Section: Introductionmentioning
confidence: 99%